Effect of variety and harvesting management on the concentration of tannins and alkaloids in tagasaste (Chamaecytisus palmensis) - Assefa, G.; Sonder, Kai; Wink, M.; Kijorad, C.; Steinmuller, N.; Peters, Kurt J. (Elsevier, 2008)
The first part of this study evaluated contents of hydrolysable tannins (HT) and condensed tannins (CT) of 65 accessions of tagasaste. In the second part, the effects of harvesting stage and growing season on the contents of HT, CT and alkaloids in different plant parts of the widely grown tagasaste variety ‘MOA’ was studied in a randomized complete block design. Regrowths of tagasaste was harvested in one experiment at 4, 6, 8 and 10 months, separated into growing buds, leaves, barks, branches and stems and in another trial at 6 months regrowth during the main rainy, dry and short rainy seasons. The leaves of different tagasaste accessions contained on average 115 g/kg dry matter (DM) HTin a range of 16–197 and 12.5 abs/g NDFCT in a range of 6.9–35.0 abs/g NDF. The edible fractions (growing buds and leaves) were higher in HT and CT contents compared to the structural parts (stems and barks). The leaf fraction contained higher HT and CT (177.2 g/kgDM and 20.1 abs/g NDF) and the HT tended to decline with progressing harvesting stages. High concentration of alkaloids was found in the non-edible fractions, with the highest content in the bark (235 mg/kg) and the lowest in the leaf (40 mg/kg DM) fractions. These levels increased in the fractions from the 4th to the 8th month of harvesting stage and then declined at the 10th month. About 90% of the alkaloids found in tagasaste were sparteine. Higher concentration of HT was found in tagasaste leaves, harvested during the rainy season compared to the dry season. The concentration of CT was low during the main rainy season, while the highest was during the short rainy and dry seasons. Contents of HT and CT were positively correlated (r = 0.25, P<0.01). However, both the HT and CT contents had negative correlation coefficient of r =−0.43 (P<0.001) and r =−0.73 (P<0.001) with alkaloids, respectively. The results of this study showed that varietal selection, and harvesting management could be used as a means to modulate the level of tannins and alkaloids in tagasaste.